Kajian Konfigurasi Escape Building Untuk Evakuasi Terhadap Bencana Tsunami Di Kota Banda Aceh - Teuku Ichsan Nurrady; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Banda Aceh is one of the cities in Sumatra that is affected by the earthquake and tsunami Andaman on 26 December 2004. Banda Aceh has a sloping and relatively flat topography, with an average height of 0.8 meters above sea level, making this city became one of the cities with The worst effects of tsunami 2004, and still have the risk of earthquakes and tsunamis in the future. It is necessary for the system in the form of vertical evacuation like escape building, so that residents can take refuge from the tsunami. However, the number and location of the escape building existing only found in the Meuraxa village, so it can not reach all areas of tsunami inundation. This research use network analyst tool to the configuration of the escape building existing to analize the service area of each escape building. From this analysis it can be known that there are still many people who are not able to reach the nearest escape building or toward a secure area before the tsunami waves arrive. The scenarios analysist simulate varying evacuation time conditions, and there are two overload escape building. The simulation result shows that the percentage of residents who are not able to reach an escape building is very small, ranging between 23.73% -10.35%, so it is considered not effective, while the analysis of the escape building existing capacity shows two escape building had excess capacity, ranging between 55.48% - 55,78%.Keywords: Banda Aceh City; service area; escape building